Afferents contributing to the exaggerated long latency reflex response to electrical stimulation in Parkinson's disease. Issue 11 (November 1988) - Hunter, J P; Ashby, P; Lang, A E
Abstract : Reflex pathways to tibialis anterior motoneurons from low threshold afferents of the common peroneal nerve were examined in 13 Parkinsonian subjects and 12 age-matched normals. Post-synaptic events occurring in single motoneurons were derived from changes in the firing probability of single voluntarily activated motor units during afferent stimulation. A period of increased firing probability of "monosynaptic" latency (about 33 ms) occurred in all subjects in both groups. A second, later, period of increased firing probability (latency about 64 ms) was seen in 2/12 normals and 8/13 Parkinsonian subjects. Neither of these responses could be produced by cutaneous stimulation. The electrical threshold of the afferents mediating the later effect was 0.82 of the threshold of alpha motoneuron axons which is similar to that of the afferents mediating the shorter latency response. Thus, large non cutaneous afferents contribute to this long latency response in man presumably through polysynaptic pathways. Transmission in these pathways is enhanced in Parkinson's disease.